2015
DOI: 10.1101/017459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abundant contribution of short tandem repeats to gene expression variation in humans

Abstract: Expression quantitative trait loci (eQTLs) are a key tool to dissect cellular processes mediating complex diseases. However, little is known about the role of repetitive elements as eQTLs. We report a genome-wide survey of the contribution of Short Tandem Repeats (STRs), one of the most polymorphic and abundant repeat classes, to gene expression in humans. Our survey identified 2,060 significant expression STRs (eSTRs). These eSTRs were replicable in orthogonal populations and expression assays. We used varian… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
137
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(147 citation statements)
references
References 71 publications
(69 reference statements)
8
137
1
1
Order By: Relevance
“…Conservative estimates suggest that in 34-41% of eQTL peaks (dependent on the population tested), the causal variant will be the top associated allele. Second, only a subset of the true variants responsible for eQTLs (23-64%, according to recent estimates) will act on enhancers or promoters, which are the functional classes that will be detected in the MPRA assay (Farh et al, 2015;Gymrek et al, 2015;Lappalainen et al, 2013). Variants that work by other processes, such as microsatellites or post-transcriptional regulation, would not be expected to score.…”
Section: Introductionmentioning
confidence: 99%
“…Conservative estimates suggest that in 34-41% of eQTL peaks (dependent on the population tested), the causal variant will be the top associated allele. Second, only a subset of the true variants responsible for eQTLs (23-64%, according to recent estimates) will act on enhancers or promoters, which are the functional classes that will be detected in the MPRA assay (Farh et al, 2015;Gymrek et al, 2015;Lappalainen et al, 2013). Variants that work by other processes, such as microsatellites or post-transcriptional regulation, would not be expected to score.…”
Section: Introductionmentioning
confidence: 99%
“…Next, polymorphic promoters STR are associated with increased variance in local gene expression and DNA methylation, suggesting functional role for STR [18]. Finally, recent studies revealed contribution of STR alleles to gene expression levels and phenotypes [9]. The functional role of STR has been demonstrated by effects on gene expression, splicing, protein sequence, and association with pathogenic effects [18].…”
Section: Polymorphic Tandem Repeats Modify Gene Expressionmentioning
confidence: 99%
“…Inherently hypervariable microsatellites modulate gene expression through several possible mechanisms, e.g. direct addition of functional DNA motifs, modification of local DNA or RNA structure, epigenetic modification of the local region, altered spacing or orientation of regulatory molecules, and alteration of nucleosome positioning [9,18].…”
Section: Polymorphic Tandem Repeats Modify Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…STRs significantly contribute to the genetic architecture of quantitative human traits and various clinically relevant conditions. 56 Dinucleotide Repeats-The most common of the microsatellite tandem repeats dispersed in the euchromatic arms of chromosomes. They consist of two nucleotides repeated in tandem; guanine and thymine, (GT)n, or (CA)n is the most frequently seen which is present at an estimated 50 000-100 000 sites per genome.…”
Section: Microsatellite Repeatsmentioning
confidence: 99%